Power system transients : theory and applications - Ametani, Akihiro; Nagaoka, Naoto; Baba, Yoshihiro; Ohno, Teruo (CRC Press, 2013)
Theory of Distributed-Parameter Circuits and the Impedance/Admittance FormulasImpedance and Admittance FormulaBasic Theory of Distributed-Parameter CircuitMulticonductor SystemFrequency-Dependent EffectTraveling WaveNon-uniform ConductorsIntroduction of EMTPSolutions of the ProblemsTransients on Overhead LinesSwitching Surge on Overhead LineFault SurgeLightning SurgeTheoretical Analysis of Transients: Hand CalculationsFrequency-Domain Method of Transient SimulationsTransients on Cable SystemsImpedance and Admittance of Cable SystemsWave Propagation and OvervoltagesStudies on Recent and Planned.